Jet transverse momentum distributions from reconstructed jets in p-Pb collisions at √s_(NN ) = 5.02 TeV - Snellman, Tomas (2019)
In this thesis we study the transverse structure of reconstructed jets via transverse fragmentation momentum, jT, distributions in proton-lead (p–Pb) collisions at the centre-of-mass energy per nucleon of 5.02 TeV. The data is measured with the ALICE experiment at the CERN LHC. In previous analysis that used two-particle correlations, it has been observed that the measured jT distributions can be factorised into two components, a narrow Gaussian component, and a wide non-Gaussian component. It was argued that these components can be linked to the non-perturbative hadronisation and to the perturbative showering process, respectively. We have observed the same factorisation holds for jT distributions obtained using reconstructed jets. Furthermore although a direct quantitative comparison is not possible, our data is qualitatively compatible with jT distributions measured from two-particle correlations. Studies of collective flow in high multiplicity p–Pb collisions have seen hints of behaviour that in Pb–Pb collisions has been taken as indication of the creation of Quark Gluon Plasma (QGP), a deconfined state of QCD matter. However studies of jet observables have shown no modification in high multiplicity p–Pb collisions. As expected it has been observed in Pb–Pb collisions that jets traversing through QGP medium will lose energy from interactions with the medium. Thus it remains an open question whether QGP is created in a p–Pb collision. In this thesis we compare measured jT distributions between minimum bias and high multiplicity p–Pb collisions. Our results show no sign of modification within the current experimental capabilities. Keywords: jet, jet shape, jet fragmentation, jet reconstruction, heavy ion, p–Pb, transverse momentum, ALICE, CERN, LHC